A conjuntura e as decisões governamentais sobre clima no estado de Mato Grosso - Lidiane Rocha de Oliveira Melo; Mario Lucio de Avila; Silvia Regina Starling Assad; Tamiel Khan Baiocchi Jacobson; Ricardo Vieira Araujo (Confins)
Understanding the territorial dynamics of land use and occupation and the administrative political implications in the decision-making process on the climate issue in the state of Mato Grosso – Brazil is the objective of this study. The authors, in bibliographic research and field studies conducted an investigation on governmental decisions in recent environmental issues in the state and how the trajectories of various sectors influence this construction. In the first part of the text there is a brief reconstruction of the occupational process of Mato Grosso, its territorial dynamics due to the expansion of agribusiness and the phenomenon of deforestation that has already consumed considerable part of the forests of the territory of the State. In the second part, the authors focus on interviews with political managers, aiming to understand the connection of the informant with the environmental theme, their perception of the environmental agenda Mato Grosso in the period from 2004 to 2015, as these perceived the Political interference in the environmental agenda and its contradictions and, finally, an exploratory approach to the different initiatives underway in the state's environmental agenda. It follows from the study a reading that dialogues with the approach of political sociology in recognizing an enlarged range of institutions and actors in the process of governmental decisions, but which is in the interests of the agribusiness sector, which dominates the local policy. As much as there is an attempt by non-governmental organizations and mixed instances to involve the environmental agenda in the Mato Grosso development, the ambiguities are still greatly emphasized by the informants.